Legal Aspects of State Asset Management: International Perspectives on Implementing State-Owned Property Law - Syamsir Syamsir; Eko Nuriyatman; Nova Bela Dhyta; Rofi Aulia Rahman; Meline Gerarita Sitompul (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
State asset management is a fundamental component of public financial governance, aimed at ensuring transparency, accountability, and efficiency. In Indonesia, the legal foundation for state asset administration is established under Law Number 1 of 2004 on State Treasury. In the context of globalization, aligning domestic regulations with international legal standards, such as the International Public Sector Accounting Standards (IPSAS), has become imperative. Discrepancies between national and international regulatory frameworks may result in legal inconsistencies, inefficiencies, and challenges in securing state assets abroad. This scholarly article employs a doctrinal legal research approach to evaluate the conformity of Indonesia’s legal framework with international standards. It identifies key challenges, including the inadequate implementation of IPSAS, deficiencies in technological infrastructure, and limited institutional capacity. Additionally, protecting state assets in foreign jurisdictions remains complex due to disparities in legal systems, bureaucratic constraints, and insufficient international legal cooperation. To address these challenges, Indonesia must reinforce its legal framework, integrate advanced technological solutions, and enhance cross-border legal collaboration. The adoption of internationally recognized best practices in state asset management will strengthen legal certainty, mitigate financial risks, and ensure compliance with global governance principles. This article contributes to the legal discourse by analyzing the complexities of state asset management in an increasingly interconnected world and proposing regulatory and institutional reforms to enhance its effectiveness.